A Study on Accounting for Suburban Agricultural Land Rent in a Chinese Context Based on Agricultural Ecological Value and Landscape Value - Keqiang Wang; Jianglin Lu; Hongmei Liu; Xin Fan; Lina Zhang; Silu Zhang (Land, 2023)
Agricultural land protection is vital for the realization of national food security and an ecological civilization. From the perspective of agricultural ecological value and landscape value, perfecting the theory of agricultural land rent is beneficial to the construction of an ecological civilization. Based on Marx’s land rent theory of agricultural production, the analytical framework of the agricultural decision support systems (DSS) was constructed; then, the agricultural land rent in suburbs was theoretically accounted for via a numerical example, and its realization rules were simulated according to the conditions of China (i.e., the specific solutions in force). Some interesting conclusions were found: (1) Agricultural production in suburbs involves both natural reproduction and social reproduction. (2) Agricultural land rent should include production land rent, ecological land rent, and landscape land rent. (3) The promotion of an ecological civilization and the development of the economy and society will lead to an increase in the comprehensive coefficient of agricultural land rent. (4) With the development of the economy, ecological land rent and landscape land rent should be gradually charged from zero payment to full payment. Based on these conclusions, five corresponding policy implications are proposed to improve the land profit of agricultural land owners to promote agricultural production, food security, and an ecological civilization.